The Influence of Employee Engagement and Job Satisfaction on Organizational Citizenship Behavior At PT. Rizki Asa Buana - Imaduddin al azzam azzam; Widya Parimita; Christian Wiradendi Wolor (LPPM Universitas Negeri Jakarta, 2021)
The objectives of this study are: 1) To find out the description of work engagement, job satisfaction and Organizational Citizenship Behavior (OCB) for employees of PT. Rizki Asa Buana on Jl. Manggul jaya no.9 (base 4) cikiwul, bantar gebang. Bekasi 17152. 2) To determine the effect of Work Engagement on Organizational Citizenship Behavior (OCB) on employees of PT. Rizki Asa Buana on Jl. Manggul jaya no.9 (base 4) cikiwul, bantar gebang. Bekasi 17152. 3) To determine the effect of Job Satisfaction on Organizational Citizenship Behavior (OCB) on employees of PT. Rizki Asa Buana on Jl. Manggul jaya no.9 (base 4) cikiwul, bantar gebang. Bekasi 17152. 4) To find out how much the contribution of Job Engagement and Job Satisfaction to Organizational Citizenship Behavior (OCB) for employees of PT. Rizki Asa Buana on Jl. Manggul jaya no.9 (base 4) cikiwul, bantar gebang. Bekasi 17152. This research was conducted on 135 employees of PT. Rizki Asa Buana on Jl. Manggul jaya no.9 (base 4) cikiwul, bantar gebang. Bekasi 17152. The data collection technique used survey and interview methods, namely by interviewing employees one by one and distributing questionnaires which were then processed using the SPSS program. This research uses descriptive and explanatory analysis. The results obtained from the regression show that there is a positive and significant influence between Work Engagement on Organizational Citizenship Behavior and a positive and significant influence between Job Satisfaction on Organizational Citizenship Behavior and the research model of Job Engagement and Job Satisfaction can predict Organizational Citizenship Behavior in Pt. Rizki Asa Buana which is on Jl. Manggul jaya no.9 (base 4) cikiwul, bantar gebang. Bekasi 17152 with a value of Fcount> Ftable (62.091> 2.70) and significance (0.000 <0.05). Keyword: Employee Engagement, Job Satisfaction, Organizational Citizenship Behavior (OCB).